Research on Structural Response Characteristics of Trapezoidal Floating Body in Waves - Song, Xuemin; Liu, Weiqin; Zhang, Guowei (Journal of marine science and engineering, 2022)
Floating structures plays an important role in extending and developing ocean resources, and their response evaluation is a hot topic of global important research due to the large dimensions. With characteristics including small depth and large horizontal plane, it is easy to induce the hydro-elastic resonant responses due to total stiffness. In this paper, first, the model design is performed to satisfy hydro-elastic similarity. Then, the model test is carried out in a wave tank to measure the structural response of a trapezoidal floating body in a series of waves. Secondly, the 3D hydro-elastic computational platform HOMER is applied to calculate the stress response of a trapezoidal floating body in numerical waves. The model test results and numerical simulation results are analyzed and compared and the conclusions are drawn, which indicate that a numerical method is effective to predict the structural response characteristics of a trapezoidal floating body. Above all, it is found that the significant response of a floating model is generated in some cases. The methods and conclusions of this study are used to provide reference and guidance for structural design of a trapezoidal floating body.